BENDERS DECOMPOSITION TO SOLVE LARGE-SCALE OF THE FACILITY LOCATION PROBLEM IN TRANSPORTATION - Dewi Hajar; Bachtiar Herdianto (Nusantara Hasana Journal, 2022)
In supply chain management and logistics systems, the transportation costs often represent an important part. The design of transportation network offers a great potential to reduce costs, time as well as improve service quality. Hence, determining the efficient solution for large-scale of transportation problems is an important task in the field of operations research, where the problem can be formulated as the Facility Location problem (FLP). The FLP seeks to locate a number of facilities to serve a number of customers. Systematic approach to the FLP have been studied in the operations research literature, yet the best possible result in rapid computational time is still unknown. Meanwhile, Benders decomposition is an exact algorithm that allows the solution of very large linear programming problems, quickly and optimally. In this research, we consider the Capacitated Facility Location Problem (CFLP). We seek to address the facility location strategy such that the location of hubs, the allocation of supplier/client nodes to hubs, as well as the inter-hub freight transportations, in order to achieve an efficient network design system. The main goal of the model is to find the global optimal solution of large-scale problem in reasonable computation time.